Development and validation of an outcome measure for orthopaedic trauma inpatients - Moghazy, Ezzat (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScPhysio (Interdisciplinary Health Sciences))--Stellenbosch University, 2008.